Compact Spectrophotometer Using TEMT600 Sensor for Protein Concentration Measurement - Matondang, Anggun Sisri Br.; Yulkifli, Yulkifli; Mairizwan, Mairizwan; Sari, Mona Berlian (Journal of Experimental and Applied Physics, 2024)
A simple spectrophotometer utilizing a white LED light source (520 nm wavelength) and a TEMT600 light sensor has been successfully developed to measure the concentration and absorbance of protein solutions. This device demonstrated an impressive average measurement accuracy of 96.26% for concentration and 95.97% for absorbance, making it highly effective for protein analysis. Despite its reliability, certain deviations were observed in the measurement results, primarily attributed to unpredictable environmental fluctuations and suboptimal sample preparation. These factors contributed to an average deviation of 3.74% for concentration and 4.25% for absorbance. While these deviations are relatively minimal and within an acceptable range, they highlight areas for potential improvement in future designs. Nevertheless, the tool is considered suitable for accurately measuring protein solution concentration and absorbance, proving its capability for laboratory or educational purposes. Its simplicity and cost-effectiveness make it a valuable device for routine protein analysis